Effects of Flaxseed (Linum Usitatissimum) As Fat Mimetics on Physicochemical and Sensory Properties of Muffin - Nurul Ashikin Mohammad Zaki; Noorlaila Ahmad; Nurul Nor Izzuani Nor Sham (Journal of Academia, 2021)
Muffin is a sweet baked product with soft texture and good taste. Egg as one of the main ingredients in muffins plays a pivotal role in maintaining nutritional and physical properties of baked products. However, eggs have high cholesterol content and are related to cardiovascular disease and hypercholesterolemia. Therefore, the aim of this study is to investigate the functional properties of seed flour, physicochemical and sensorial properties of muffin with flaxseed (Linum usitatissimum) as egg substitute at different concentrations. Egg was substituted with flaxseed at 25, 50, 75 and 100% whilst control muffin contains 100% egg. The percentage of emulsifying capacity, emulsion stability, water holding capacity and oil binding capacity of flaxseed flour were 9.42% ±1.36, 8.02% ±0.27, 472% ±2.65 and 222.67% ±2.52 respectively. Meanwhile, the protein content and fat content in muffin decreased with an increase of flaxseeds but ash, fiber and carbohydrate showed an increase at higher percentage of flaxseed substitutions. The calorie content for muffin substituted flaxseed decreased between 3.83 - 7.83%. The flaxseed substituted muffin also has a lower value for hardness (1279.00 ±3.61g) at 25% substitution and 720.67 ±4.04g at 100% substitution as compared to control muffin with the significantly highest (p<0.05) hardness value of 1638.00 ±7.21g. Sensory evaluation indicated that muffin with 25-100% flaxseed substitution showed non-significant difference with control sample in taste, texture and overall acceptability. Therefore, flaxseed is suitable as an egg substitute in the production of muffin with high nutritional value and acceptable sensory characteristics.